Emergency contraception among female regular undergraduate students of Debre Markos University - knowledge, attitude, utilization, and associated factors, 2021: a cross-sectional study: Emergency contraception among female regular undergraduate students - Getinet, Mamaru (Ethiopian Journal of Reproductive Health, 2022)
Introduction: Emergency contraception is a type of modern contraception used to prevent pregnancy after a sexual act that is either unprotected or insufficiently protected. Conceived failure, condom breakage, missed doses of oral contraceptives, and failure to utilize any method of contraception are all common reasons for emergency contraception. To prevent such problems, emergency contraceptives are the only method that can be used after unprotected sex. Therefore, this study aimed to determine the knowledge, attitude, and practice of emergency contraception in the study area. Methods: Institutional based cross-sectional study using multistage stratified sampling was conducted at Debre Markos University from June 27 to July 15, 2021. A sample size of 446 students was proposed for the study and a self-administered questionnaire was used for data collection. Data were entered to EPI INFO and translated to SPSS for window version 26 for data analysis. Multiple logistic regressions were employed to describe the strength of the association between the selected study variables by controlling the effect of possible confounders Result: The majority of the participants (74.4%) reported that they had heard about EC. Out of those who heard about emergency contraceptives, 58.1% identified oral pills as a possible method of emergency contraceptive, followed by injectable 18%. Around half, 207 (46.7%) of the study participants indicated that they recommended others to use ECs. Among the respondents who had ever heard of EC, almost one-fourth 104 (23.3%) of them had ever used EC Pills. The Father's educational level, field of study, and year of study showed a significant association with good knowledge of EC in multivariate logistic regression analysis. There is a strong association between the field of study, marital status, and knowledge about emergency contraceptive communication with the practice of emergency contraception. Conclusions and recommendations: This study showed that the awareness of emergency contraception among respondents was fair. Moreover, their attitude to using emergency contraception and to advising others to use and their practice is low. Therefore, further to increase the knowledge, attitude, and practice of emergency contraception user-friendly services, basic training about reproductive health and family communication services should be promoted.